Korelasi Genetik Antara Bobot Sapih dengan Bobot Satu Tahun dan Laju Pertumbuhan Pasca Sapih Sapi Brahman Cross - Gushairiyanto, Gushairiyanto; Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
Increased  production  of  meat  has  to  be  done  to  meet  the  needs  of  the  animal  protein  demand continues  to  increase,  this  study  aims  to  look  at  the  possibility  of  accelerating  the  implementation  of selection with respect to the production of meat that is when the cow weaned in order to improve respos selection.  This  study  collected  data  includes  birth  weight,  weaning  weight,  weight  of  one  year  and  post-weaning growth rate and identify the lineage of every cow that became the object of research. The study was conducted by analyzing the data to obtain heritability value weaning weight, weight of one year and post-weaning growth rate and the value of genetic correlation between cow weight and weight one year post-weaning growth rate.  The results showed heritability values weaning weight, weight of one year and post-weaning growth rate  include  high  category,  respectively  were  0.62 ±  0.40,  1.05  ±  0.59  and  1.25  ±  0.63.  The  value  of genetic correlation between weaning weight and weight one year post-weaning growth rate was positive and included high category, each is 0.51 and 0.55. This means that selection on weaning weight increase will  be  followed  also  by  the  increasing  weight  of  one  year  and  post-weaning  growth  rate,  selection  on weaning  weight  will  accelerate  the  implementation  of  selection  of  the  parameters  related  to  meat production, so as to increase the selection response per year.